Dealmaking Disrupted: The Unexplored Power of Social Media in Negotiation. Issue 1 (19th January 2021) - Sebenius, James K.; Cook, Ben; Lax, David; Fortgang, Ron; Silberberg, Isaac; Levy, Paul
Abstract: While social media has had profound effects in many realms, the theory and practice of negotiation have remained relatively untouched by this potent phenomenon. In this article, we survey existing research in this area and develop a broader framework for understanding the wider roles and effects of social media on negotiation. Through a series of detailed case studies, we explore how social media can drive important negotiations either off the rails or toward beneficial outcomes—and how savvy practitioners can harness this often‐neglected factor to their advantage, or else find themselves outmaneuvered by more digitally sophisticated parties. Applying the lens of the "3D negotiation" approach developed by Lax and Sebenius, we describe a number of potentially decisive roles that social media can play to enhance actions by negotiators "at the table, " with respect to deal design, and "away from the table." In this 3D context, we show how social media can help negotiators learn about their counterparts (interests, perceptions, relationships, and networks), directly and indirectly influence the parties, mobilize supporters, and neutralize potential opponents. We show that being proactive—both in cultivating digital influence or allies and in building resilience to threats across online information ecosystems—can provide critical advantages for negotiators navigating a hyperconnected world. We develop a preliminary framework to help identify the full range of platforms, tools, and methodologies appropriate for the use of social media in negotiations, including network mapping software and open‐source intelligence techniques. Throughout our analysis, we stress the importance of ethical and privacy considerations.